2021
DOI: 10.1111/oik.07694
|View full text |Cite
|
Sign up to set email alerts
|

A trait‐based approach predicting community assembly and dominance of microbial invasive species

Abstract: Understanding the mechanisms underlying community assembly helps to define success and susceptibility to biological invasions. Here, we explored phytoplankton community assembly following niche and neutral paradigms and using a trait-based approach. Under the hypothesis that the morphology-based functional groups (MBFG) clusters species with similar niche, we analysed how trait-related differences in fitness influence dominance of an invasive species. This was based on literature review, field data and model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 115 publications
0
14
1
1
Order By: Relevance
“…furcoides were absent. The data from the present study, however, are not sufficient to support the suggestion of an alternation between these phytoplankton taxa (Kruk et al, 2021; Roriz et al, 2019), nor their coexistence in the environment (Reynolds et al, 2002). Further, the physical, chemical and consequently biological variability exhibited marked changes attributable to rainfall in a typical run‐of‐the‐river shallow reservoir such as Paracambi (Branco et al, 2019).…”
Section: Resultscontrasting
confidence: 93%
“…furcoides were absent. The data from the present study, however, are not sufficient to support the suggestion of an alternation between these phytoplankton taxa (Kruk et al, 2021; Roriz et al, 2019), nor their coexistence in the environment (Reynolds et al, 2002). Further, the physical, chemical and consequently biological variability exhibited marked changes attributable to rainfall in a typical run‐of‐the‐river shallow reservoir such as Paracambi (Branco et al, 2019).…”
Section: Resultscontrasting
confidence: 93%
“…Our results showed that K. humilis developed adaptive strategies in response to different grazing disturbances, with significant differences observed in monocot biomass and material partitioning patterns among the different grazing treatments. The plants improved their adaptation to grazing by adjusting resource allocation to occupy a favorable ecological niche in a continuously disturbed environment (Kruk et al, 2021). In our study, the S+Y treatment resulted in the highest biomass per plant, while the Y treatment showed the lowest biomass per plant.…”
Section: Morphological Changes Of K Humilis In Response To Individual...mentioning
confidence: 50%
“…Whereas the classic ecological models typically assume a constant environment, trait-based models focus on community dynamics along major environmental gradients. The system dynamics created by interaction between various ‘guilds’ and their environment may lead to a functional trait distribution that optimises a certain community-level functional property, such as nitrification in soil systems [ 110 , 111 ], organic matter decomposition [ 109 , 112 ], or resilience to invasion [ 113 ]. Trait-based models can elucidate the emergence of selection pressures and diversity patterns along modelled environmental gradients - important aspects to understanding evolutionary processes [ 114 , 115 ].…”
Section: Ecological Modelsmentioning
confidence: 99%